MICRO BUSINESS STUDY OF TRADITIONAL HEALTH DRINK PRODUCTS “TELANG LIMAO BANGKAK” (GREEN BUSINESS CANVAS STUDY “ECOCANVAS”) - Muhammad Alfarizi; Rini Kurnia Sari (Food ScienTech Journal, 2021)
This study aims to formulate a business development strategy that is appropriate and can be applied to the traditional Indonesian health drink business "Telang Limao Bangkak" which is a combination of Bunga Telang and Limao Calong Bangka (Orange Key). The research method used is descriptive qualitative analysis. Data collection was carried out using interview and assessment questionnaire techniques. The results of this study indicate that the position of the health drink business "Telang Limao Bangkak" is in the very profitable position of the Aggressive quadrant. The strategy implemented is to support an aggressive growth policy (growth-oriented strategy) and has been implemented in the EcoCanvas Health Drink business model "Telang Limao Bangkak". The results of this research are expected to create a new air of green business that gives birth to health drink products that will improve people's welfare.